2008
DOI: 10.1007/s10549-008-0025-2
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic imaging in neoadjuvant chemotherapy of locally-advanced breast cancer should be cost-effective

Abstract: Introduction-The use of neoadjuvant chemotherapy in cases of locally advanced breast cancer has been steadily increasing, and is also in wider use for other cancers. As a consequence, a growing number of studies have focused on the question of how best to assess the therapeutic response to various chemotherapy or systemic therapy regimens. Prognostic imaging of response to therapy early in the course of a planned chemotherapy regimen could be of considerable value, particularly if shifting to another therapy r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 19 publications
0
20
0
1
Order By: Relevance
“…9 For example, scintimammography with technetium-99m ͑Tc-99m͒ sestamibi can detect large multifocal lesions and metastases, 10 but investigational breast-specific gamma imaging devices are necessary to visualize tumors smaller than 1 cm. 11 Positron emission tomography ͑PET͒ is another functional modality that has the added advantage of quantifying radiotracer uptake, allowing accurate diagnosis, staging, and treatment re-sponse evaluation of advanced breast cancers, [12][13][14][15] but the resolution of conventional PET scanners limits the sensitivity of this modality for detecting lesions smaller than 5-10 mm. Positron emission mammography ͑PEM͒ is an emerging functional imaging modality that is dedicated to positron emission imaging of the breast, with the purpose of achieving higher sensitivity than PET to earlier stages of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…9 For example, scintimammography with technetium-99m ͑Tc-99m͒ sestamibi can detect large multifocal lesions and metastases, 10 but investigational breast-specific gamma imaging devices are necessary to visualize tumors smaller than 1 cm. 11 Positron emission tomography ͑PET͒ is another functional modality that has the added advantage of quantifying radiotracer uptake, allowing accurate diagnosis, staging, and treatment re-sponse evaluation of advanced breast cancers, [12][13][14][15] but the resolution of conventional PET scanners limits the sensitivity of this modality for detecting lesions smaller than 5-10 mm. Positron emission mammography ͑PEM͒ is an emerging functional imaging modality that is dedicated to positron emission imaging of the breast, with the purpose of achieving higher sensitivity than PET to earlier stages of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Thirty-three articles were selected and retrieved in fulltext version (Figure 1). One study was found screening the references [6] and 18 articles were subsequently excluded [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] . Finally, 16 studies were included [6,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] .…”
Section: Resultsmentioning
confidence: 99%
“…Attempting to utilize a single time point in the treatment cycle to predict response may not be the ideal, and repeating the MBI shortly after switching to the second chemotherapeutic agent may be worth evaluating. A cost-effectiveness model reported by Schegerin et al 29 showed that even a small improvement in cure rate with NAC would generally outweigh the cost of prognostic imaging. Direct conversion–MBI is a relatively inexpensive imaging procedure (approximately 1.5 times that of digital mammography).…”
Section: Discussionmentioning
confidence: 99%